ANALISIS STRATEGI GENERIK DALAM INDUSTRI PERBANKAN DI INDONESIA - Akhmad Muhammadin; Rashila Ramli; Nuramal Nuramal (P3M STIEM BONGAYA, 2018)
The purpose of this study is, to analyze conceptually and generic strategy theory whichincludes differentiation strategies, low cost strategies and focus strategies in the banking industry inIndonesia. The influence of structure in generic strategy analysis on the banking industry in Indonesiais very varied. This analysis requires a comprehensive approach and requires an integrated approach.Generic strategy analysis provides an overview problems faced in measuring and evaluating theinternal conditions faced by the company, especially service sector companies namely the bankingindustry with regard to products, costs and focus on running a business. This research can alsodetermine the extent of the bank's actions to win the competition, and provide appropriate conditionsto achieve the company's goals.